2013
DOI: 10.1021/jf403523g
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Ginger Essential Oil against Alcoholic Fatty Liver in Mice

Abstract: Fatty liver is significantly associated with hepatic cirrhosis and liver cancer. Excessive alcohol consumption causes alcoholic fatty liver disease (AFLD). Ginger has been reported to exhibit antioxidant potential and hepatoprotective activity. In the present study, a mouse model for AFLD was developed by employing male C57BL/6 mice that were fed an alcohol-containing liquid diet (Lieber-DeCarli diet) ad libitum. In the treatment groups, ginger essential oil (GEO) and citral were orally administered every day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…The ginger essential oil and citral exhibited hepatoprotective activity against AFLD in mice. The amounts of metabolites in serum such as D-glucurono-6,3-lactone, glycerol-3-phosphate, pyruvic acid, lithocholic acid, 2-pyrocatechuic acid, and prostaglandin E l increased after alcohol administration, but the levels were recovered in treatment groups [80]. Therefore, ginger could be used as a candidate to the prevention and treatment of hangover and organ damages induced by overconsumption of alcohol through its antioxidant action.…”
Section: Zingiber Officinalementioning
confidence: 99%
See 1 more Smart Citation
“…The ginger essential oil and citral exhibited hepatoprotective activity against AFLD in mice. The amounts of metabolites in serum such as D-glucurono-6,3-lactone, glycerol-3-phosphate, pyruvic acid, lithocholic acid, 2-pyrocatechuic acid, and prostaglandin E l increased after alcohol administration, but the levels were recovered in treatment groups [80]. Therefore, ginger could be used as a candidate to the prevention and treatment of hangover and organ damages induced by overconsumption of alcohol through its antioxidant action.…”
Section: Zingiber Officinalementioning
confidence: 99%
“…Mice Amelioration of liver and brain alcohol injuries through decreasing L-γ-glutamyl transpeptidase and butyryl cholinesterase [76] Humans Decreased signs and symptoms of alcohol hangover [79] Essential oil and citral Mice Hepatoprotective property against AFLD by decreasing levels of D-glucurono-6,3-lactone, glycerol-3-phosphate, and pyruvic acid in serum [80] Opuntia ficus-indica Flavones and phenolics Cladode Humans Reduced hangover symptoms by inflammatory mediator production inhibition [88,89] Rats Suppression of liver damage induced by alcohol through ending free radical chain reactions or enhancing the endogenous antioxidant activities [90] Panax ginseng Ginsenosides Root Humans Relief from hangover symptoms through reduced expiratory and plasma alcohol levels and hangover severity [91] Linoleic acid Mice Alleviation of hangover through reduced alcohol and acetaldehyde levels and enhanced ADH and ALDH activities [92] Mice Suppressed alcohol-induced toxicity on male fertility [93] Ricefish Suppressed alcohol-induced toxicity on embryogenesis [94] Mouse embryos Suppressed alcohol-induced toxicity in the neurocranium through its effects on antioxidant activity [95] Rats Suppressed alcohol-induced toxicity in the gastric system via the restoration of heat-shock proteins [96] Hypericum perforatum Hypericin and hyperforin Leave and flowering tops Rats and mice Reduced voluntary alcohol intake in acute and chronic alcohol treatment through neurochemical mechanisms [101,104,105] Rats Attenuated alcohol withdrawal syndrome by inhibition of the effects on tremors and audiogenic seizures [102] Salvia miltiorrhiza…”
Section: -Gingerol Rhizomementioning
confidence: 99%
“…The integral view of metabolomics is exactly consistent with the holistic thinking of TCM and comprehensive actions of herbal medicines (Wang et al, 2012b). Thus, metabolomics offers a novel and promising approach to assess the therapeutic effects of herbal medicines and elucidate their underlying mechanisms (Gou et al, 2013;Liu et al, 2013;Sun et al, Bedford, MA, USA). All other chemicals were of analytical grade.…”
Section: Introductionmentioning
confidence: 83%
“…33 As is well known, acetoacetate is produced 46 In our study, the observed increases in acetoacetate and acetone may be related to the upregulation of fatty acid oxidation in the model rats. 48 The excessive accumulation of acetate in the model rats revealed the disordered conversion systems of acetate-acetyl-CoA, which further inuenced the citric acid cycle. We also noted an elevated concentration of acetate in the model rats, which is a product not only of fatty acid oxidation in peroxisomes but also of alcohol metabolism.…”
Section: Discussionmentioning
confidence: 99%